1981
DOI: 10.1128/jb.147.2.602-611.1981
|View full text |Cite
|
Sign up to set email alerts
|

Localization of enterobacterial common antigen in Yersinia enterocolitica by the immunoferritin technique

Abstract: Rabbits were immunized with the enterobacterial common antigen (ECA)-immunogenic strain Escherichia coli F470. ECA-specific antiserum was obtained by absorbing the resulting antisera with the genetically closely related ECA-negative strain E. coli F1283. These two strains also served as positive and negative controls in the localization study of ECA in Yersinia enterocolitica strain 75, smooth and rough forms (Ye75S and Ye75R), by the indirect immunoferritin technique. Cells of Ye75S grown at 22 degrees C show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 20 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Therefore, it is assumed that Ospecific chains cover ECA in Ye 75S cells cultivated at 22 ° C, but to a much lesser extent in the 40 ° C culture when a high amount of rough LPS is present. Correspondingly, a much higher label density is found in an (incomplete) R mutant (Ye 75R) of this strain [49].…”
Section: Localization Of Eca In the Bacte-rial Cellmentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, it is assumed that Ospecific chains cover ECA in Ye 75S cells cultivated at 22 ° C, but to a much lesser extent in the 40 ° C culture when a high amount of rough LPS is present. Correspondingly, a much higher label density is found in an (incomplete) R mutant (Ye 75R) of this strain [49].…”
Section: Localization Of Eca In the Bacte-rial Cellmentioning
confidence: 76%
“…Earlier studies on the LPS of this strain showed by SDS-polyacrylamide gel electrophoresis (SDS-PAGE), that the number of (Ounsubstituted R-core stubs is drastically increasing when cells are grown at higher temperatures [48]. With regard to ECA, a definite label is visible in electron microscopy with Yersinia enterocolitica (Ye 75S) grown at a high temperature (40 o C) but no ferritin label at all is observed with cells grown at 22°C [49]. Therefore, it is assumed that Ospecific chains cover ECA in Ye 75S cells cultivated at 22 ° C, but to a much lesser extent in the 40 ° C culture when a high amount of rough LPS is present.…”
Section: Localization Of Eca In the Bacte-rial Cellmentioning
confidence: 94%
“…Recently, the chemical structure of the inner core polysaccharide composed of seven sugar residues was determined (Radziejewska-Lebrecht et aL, 1994) and preliminary structural analysis showed that there are six sugar residues in the outer core (J. Radziejewska-Lebrecht, M. Skurnik, A. S. Shashkov, and H. Mayer, unpublished). The expression of the hornopolymeric O-antigen is temperature regulated such that the number of repeating units per LPS molecule is higher when bacteria are grown at 22°C (Acker et aL, 1981;AI-Hendy et al, 1991b;Kawaoka et al, 1983;Wartenberg et aL, 1983). Acker and co-workers (Acker et al, 1981) demonstrated that the enterobacterial common antigen (ECA) of Y. enterocolitica serotype 0:3 strain was sterically blocked by abundant O-antigen from ECA-specific antibody molecules in bacteria grown at 22°C but not in bacteria grown at 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the hornopolymeric O-antigen is temperature regulated such that the number of repeating units per LPS molecule is higher when bacteria are grown at 22°C (Acker et aL, 1981;AI-Hendy et al, 1991b;Kawaoka et al, 1983;Wartenberg et aL, 1983). Acker and co-workers (Acker et al, 1981) demonstrated that the enterobacterial common antigen (ECA) of Y. enterocolitica serotype 0:3 strain was sterically blocked by abundant O-antigen from ECA-specific antibody molecules in bacteria grown at 22°C but not in bacteria grown at 37°C. For a number of years we have conducted studies on the genetics of the lipopolysaccharide biosynthesis and regulation of Y. enterocolitica (AI-Hendy et al, 1991a,b;Skurnik and Toivanen, 1993;Zhang et aL, 1993) and, during these studies, became interested in the temperature regulation of the O-antigen.…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter alternative might not be valid as the bacteria are most likely degraded and processed by rabbit antigen-presenting cells during immunization. Acker et al reported that on whole bacteria, ECA is better exposed on the cell surface of Rc mutant Ye75R bacteria than on the parental S strain Ye75S bacteria ( Acker et al 1981 ).…”
Section: Resultsmentioning
confidence: 99%